2002
DOI: 10.1212/wnl.58.12.1843
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin improves lid opening delays in blepharospasm-associated apraxia of lid opening

Abstract: Lid movement and EMG of the orbicularis oculi (OOc) were analyzed in 10 patients with apraxia of lid opening associated with blepharospasm before and after botulinum toxin treatment. The latencies to onset and to complete the eye opening and the time during which eye opening was sustained were studied in relation to OOc activity and compared with control values obtained in 12 healthy subjects. Following treatment there was an improvement of all lid opening measurements, a decrease of the abnormally prolonged O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Many studies have demonstrated moderate or marked improvement in more than 90% of patients with blepharospasm, particularly when BOTOX is injected into the pretarsal portion of the orbicularis oculi of the upper and lower eyelids [40]. When compared with 12 healthy subjects, there was an improvement in lid opening and a reduction of functional disability in ten patients with a combination of blepharospasm and apraxia of eyelid opening when treated with BOTOX [41]. EMG of the orbicularis oculi muscles in the treated subjects demonstrated decreased latencies in eye opening and increased time of sustained eye opening in comparison to pretreatment measurements.…”
Section: Blepharospasm and Apraxia Of Eyelid Openingmentioning
confidence: 99%
“…Many studies have demonstrated moderate or marked improvement in more than 90% of patients with blepharospasm, particularly when BOTOX is injected into the pretarsal portion of the orbicularis oculi of the upper and lower eyelids [40]. When compared with 12 healthy subjects, there was an improvement in lid opening and a reduction of functional disability in ten patients with a combination of blepharospasm and apraxia of eyelid opening when treated with BOTOX [41]. EMG of the orbicularis oculi muscles in the treated subjects demonstrated decreased latencies in eye opening and increased time of sustained eye opening in comparison to pretreatment measurements.…”
Section: Blepharospasm and Apraxia Of Eyelid Openingmentioning
confidence: 99%
“…EMG studies have shown that in normal subjects the neuromuscular activity of the pretarsal orbicularis oculi is undetectable. In contrast, during clinical examination of ELA patients, persistent activity of the pretarsal orbicularis oculi was recorded, suggesting that it is a major factor interfering with eyelid opening in most patients with ELA [14]. In ELA patients, it is suggested that, on trying to open the eyes, persistent inhibition of orbicularis oculi activity is related to the time for complete eyelid opening [14].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, during clinical examination of ELA patients, persistent activity of the pretarsal orbicularis oculi was recorded, suggesting that it is a major factor interfering with eyelid opening in most patients with ELA [14]. In ELA patients, it is suggested that, on trying to open the eyes, persistent inhibition of orbicularis oculi activity is related to the time for complete eyelid opening [14]. Persistent contraction of Riolan’s muscle may increase the threshold for triggering contraction of the levator palpebrae superioris muscle and thereby interfere with voluntary opening of the eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Injection of 4-5 units of botulinum toxin A into several sites around the pretarsal orbicularis oculi muscle has been shown to elicit an improvement in eyelid opening, with the sites of most effectiveness being between the preseptal and pretarsal portions of the orbicularis oculi (Vissenberg et al 1993 ;Forget et al 2002 ) . On average, symptoms improve for 2 months, with retreatment necessary after this time period to maintain improved eyelid control.…”
Section: Apraxia Of Eyelid Opening (Atypical Blepharospasm)mentioning
confidence: 99%